Notice for Chairman of ABC Ltd. to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter for BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding notice for Chairman of ABC Ltd. to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter for BRAC University new campus project.